Pengaruh Sikap Wajib Pajak Pada Sistem Pajak dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Adopsi Sistem Pajak Elektronik Sebagai Variabel Mediasi Pada KPP Pratama Cilegon - Dadan Ramdhani; Zahra Alya Tamima; Yanti Yanti; Bahtiar Effendi (Universitas Matana, 2022)
This study aims to determine the effect of taxpayer attitudes on the tax system and tax socialization on individual taxpayer compliance with the adoption of the electronic tax system as a mediating variable at KPP Pratama Cilegon. The population used is an individual taxpayer registered at KPP Pratama Cilegon. This research is a type of quantitative research. The sampling method used in this study is incidental sampling with a sample of 102 individual taxpayers who are registered as mandatory SPT at KPP Pratama Cilegon. This study uses primary data obtained from questionnaires. The analytical method used in this study is PLS-SEM using the SmartPLS version 3.2.9 application. The results show that the attitude of taxpayers to the tax system has a positive and significant effect on individual taxpayer compliance, tax socialization has a positive and significant effect on individual taxpayer compliance, taxpayer attitudes on the tax system have a positive and significant effect on the adoption of the electronic tax system, taxation socialization has a positive and significant effect on the adoption of an electronic tax system, the adoption of an electronic tax system has a positive and significant effect on individual taxpayer compliance, the adoption of an electronic tax system can mediate the effect of taxpayer attitudes on the tax system on partial individual taxpayer compliance and adoption electronic tax system can partially mediate the effect of tax socialization on individual taxpayer compliance.